Design optimization of Bi-tubular thin walled columns for crashworthiness application - Tarlochan F. (Trans Tech Publications Ltd, 2023)
Improving crashworthiness of vehicles is considered to be one of the main concerns in traffic safety. The study focused on new designs that can be incorporated into existing vehicles. The paper presents a crashworthiness design of a bi-tubular thin walled column for different dimension profiles. To formulate the complex crashworthiness design problem, the response surface method (RSM) was utilized. The design of experiments of the factorial design is used to construct the response surface for the specific energy absorption (SEA). This surface was optimized for SEA. Results from a finite element analysis of elastic plastic square bi-tubular steel tubes subjected to dynamic axial impact load are reported. The bi-tubular design has shown good potential as an efficient energy absorber in comparison to existing conventional energy absorbing structures. (2011) Trans Tech Publications.